Interaction time and beam diameter effects on the conduction mode limit - Assunção, Eurico; Williams, Stewart W.; Yapp, David (Elsevier Science B.V., Amsterdam., 2012)
Laser welding has two distinctive modes: keyhole and conduction mode. Keyhole mode is characterized by deep penetration and high welding speeds, while conduction mode has higher quality welds with no defects or spatter. This study focuses on the transition from conduction to keyhole mode by increasing power density and using different beam diameters and interaction times. Based upon the results it was possible to evaluate that there is a transition mode between conduction and keyhole mode. The results show that the transition between conduction and keyhole mode is not defined by a single power density value. This transition has a range of power densities that depend on the beam diameter and on the interaction time. This study allows the identification of the power density that limits conduction mode, based on parameters such as beam diameter and interaction time instead of a single power density value independent of these parameters.
Keywords: Laser welding; Keyhole mode; Conduction mode